The Effect of Early Skin-to-skin Contact on the Mental Health of Mothers in Traumatic Childbirths - Abdollahpour 1, Sedigheh; Bolbolhaghighi 2, Nahid; Khosravi 3*, Ahmad (Shahroud Journal of Medical Sciences, 2017)
Background: Providing and sustaining the mental health of mothers who have experienced a traumatic childbirth have significant impact on the health of the mother, family and society. This study aimed to evaluate the effect of early skin-to-skin contact in the first hour of birth on the mental health of mothers with traumatic childbirth. Methods: This randomized clinical trial was conducted in 2015 on 82 mothers who, based on Diagnostic and Statistical Manual of Mental Disorders (DSM-V-TR) criteria, had experienced a traumatic childbirth. After randomly assigning mothers into groups, the intervention group received early skin-to-skin contact in the first hour after birth, and the control group received the routine procedures. The mental health as an outcome of this study was evaluated using the Persian version of General Health Questionnaire (GHQ-28). Results: The results showed that the mean score of mental health of mothers in the intervention and control groups was significantly different (P < 0.001) and with the passage of time, the mental health status in the intervention group appeared better than that of the control group (P < 0.001).Conclusions: Early skin contact in the first hour of birth not only in normal deliveries but also in traumatic births can have an important and effective role in improving the mental health of the mother